Milan, Genoa and the Alps: early medieval exchanges across a region (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
In this contribution I consider how Milan and its inhabitants were connected both north and south in the early medieval period. I focus on exchanges understood as giving and receiving, buying and selling, leasing and renting, but also encompassing the more general sense of cultural interchange. All such exchanges certainly helped to connect one place (or region) to another both physically and conceptually. As the connectedness of Milan to its hinterland was one of the main themes of my recent book The Lands of Saint Ambrose (2019) I deal with that in the second part of this chapter, as the formation of a large hinterland was a fundamental part of Milan’s importance as a settlement in the early medieval period. One question I address throughout, is whether there were any significant connections between those who lived in the city and those who visited it from elsewhere, especially, given the theme of this conference, from north of the Alps. Another aspect of the same question though is how or if the Mediterranean was connected to the north via Milan.
Keywords: Milan; Hinterland; Saint Ambrose; Alps; Mediterranean